Lidocaine Ameliorates Diabetic Peripheral Neuropathy in Streptozotocin-Induced Diabetic Rats through Modulating the c-Jun Signaling Pathway. (17th August 2022) - Luo, Jinyu; Wu, Dedan; Wu, Qianming; Chen, Yan; Gan, Yong; He, Meng; Sun, Wenyangming; Ai, Yiqin; Su, Qiuping; Zou, Xiaohua; Wang, Dashou
Abstract : As one of the common complications of diabetes mellitus (DM), Diabetic Peripheral Neuropathy (DPN) threatens human lives seriously. Emerging evidences have confirmed the protective effects of lidocaine on DPN. However, the possible role and underlying mechanisms of lidocaine in DPN have not been clarified. In this study, the potential role of lidocaine in DPN is explored, and the possible mechanisms are investigated. The rat DPN model is constructed through administration of streptozotocin (STZ, 60 mg/kg). All rats are randomly divided into four groups, including the control group, DPN group, lidocaine (3.78 mg/time) group, and lidocaine combined with the SP600125 (15 mg/kg) group. Mechanical threshold, thermal latency, and blood glucose of rats before and after treatment are detected, and Nerve Conduction Velocity (NCV) is assessed. Moreover, qRT-PCR and western blot assays are carried out to determine the expressions of the c-Jun signaling pathway. The experimental results demonstrate that lidocaine remarkably downregulates the mRNA and protein expressions of the c-Jun signaling pathway in serum and DRGs induced with DPN. Besides, lidocaine combined with SP600125 can obtain better effects than lidocaine alone. It is clearly evident that lidocaine has a certain therapeutic effect on DPN.